2016
DOI: 10.1021/acscentsci.6b00162
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Reactivity to Biological Macromolecules with a Deep Multitask Network

Abstract: Most small-molecule drug candidates fail before entering the market, frequently because of unexpected toxicity. Often, toxicity is detected only late in drug development, because many types of toxicities, especially idiosyncratic adverse drug reactions (IADRs), are particularly hard to predict and detect. Moreover, drug-induced liver injury (DILI) is the most frequent reason drugs are withdrawn from the market and causes 50% of acute liver failure cases in the United States. A common mechanism often underlies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(140 citation statements)
references
References 70 publications
1
139
0
Order By: Relevance
“…Our previous studies with the AMD have observed comparable drops in site-level (equivalent to the pair-level in this study) to molecule-level accuracy. 41,44,45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies with the AMD have observed comparable drops in site-level (equivalent to the pair-level in this study) to molecule-level accuracy. 41,44,45 …”
Section: Resultsmentioning
confidence: 99%
“…83 Consequently, in future work we plan to incorporate the quinone formation model with already-developed reactivity models. 44,45 …”
Section: Model Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoon et al [101] demonstrated that predicting the primary cancer site from cancer pathology reports together with its laterality substantially improved the performance for the latter task, indicating that multi-task learning can effectively leverage the commonality between two tasks using a shared representation. Many studies employed multi-task learning to predict chemical bioactivity [387,391] and drug toxicity [392,541]. Kearnes et al [385] systematically compared single-task and multi-task models for ADMET properties and found that multi-task learning generally improved performance.…”
Section: Multimodal Multi-task and Transfer Learningmentioning
confidence: 99%
“…Known sites of metabolism are marked with white circles. The metabolism and reactivity 91 predictions are plotted against each atom in the molecule, with color shading ranging from red (1.0, likely) to white (0.0, unlikely). Structural alerts indiscriminately flag both bioactivated and not-bioactivated compounds as problematic.…”
Section: Figurementioning
confidence: 99%